New reference values for echocardiographic dimensions of healthy Dutch children. - Overbeek LIH; Kapusta L; Peer PGM; de Korte CL; Thijssen JM; Daniels O (European Journal of Echocardiography, 2006)
AimTo renew the echocardiographic reference values of heart dimensions in healthy children.Methods and resultsGroup 1 consisted of 587 children, of which 361 boys and 226 girls, age from birth to 18 years, body weight over 2500 g, who visited the Pediatric Cardiology outclinic during the period January 2000 till March 2004. All included children were diagnosed as normal, or as having innocent heart murmur. The second group was taken from an earlier study and comprised 160 children (77 boys and 83 girls). The echocardiographic measures were taken from conventional M-mode recording of the left ventricle (LV) parasternal long axis view. End diastolic septal (IVS) and LV posterior wall thickness (LVPW) and end diastolic as well as end systolic LV intracavity dimensions were retrospectively analyzed. The regression lines from all measured sizes are significantly different from those collected in the early eighties. Especially the thickness of the IVS is smaller. The regression lines are independent of gender.ConclusionsNew reference values have been found which should replace the presently used ones. There is no difference between boys and girls. Why the muscular wall thicknesses are thinner than found 20 years ago needs to be further explored.